The Influence of Kardinah School Innovation on Community Satisfaction - Hari Satopo; Dien Noviany Rahmatika; Teguh Budi Raharjo; Ahmad Hanfan (Educia Journal, 2026)
This study examines the influence of the Sekolah Kardinah innovation on community satisfaction at Kardinah Regional Hospital, Tegal City. Sekolah Kardinah is an integrated childcare and early childhood education service designed to support patients and families during healthcare visits. Using a quantitative correlational approach, data were collected from 120 service users through a structured questionnaire and analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The findings indicate that Sekolah Kardinah innovation positively and significantly affects community satisfaction. Human resource quality and service safety emerged as the most important dimensions contributing to positive user experiences. The innovation also enhanced comfort, trust, and willingness to reuse the service. The study highlights the importance of family-centered service innovation in creating public value and improving healthcare experiences. The findings contribute to the literature on public service innovation and healthcare management by demonstrating how cross-sector integration between healthcare and education can strengthen community satisfaction and organizational performance.